A prospective study of chemotherapy immunologic effects and predictors of humoral influenza vaccine responses in a pediatric oncology cohort. Issue 6 (30th November 2012) - Kersun, Leslie S.; Reilly, Anne; Coffin, Susan E.; Boyer, Jean; Luning Prak, Eline T.; McDonald, Kenyetta; Hou, Xiaoling; Jawad, Abbas F.; Sullivan, Kathleen E.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Kersun et al. (2013) A prospective study of chemotherapy immunologic effects and predictors of humoral influenza vaccine responses in a pediatric oncology cohort. Influenza and Other Respiratory Viruses 7(6), 1158–1167. Background: Pediatric oncology patients represent a cohort of individuals uniquely at risk of complications from influenza, yet less likely to respond to the vaccine. It is not yet clear how to best protect this vulnerable population. Methods: We performed a prospective analysis of 177 pediatric oncology patients to define the predictors of influenza vaccine responses. Each variable was examined over three time points and a repeated measure analysis was performed. Results: Patients with ALL vaccinated during induction phase had superior influenza vaccine responses than those subjects vaccinated during post‐induction or maintenance phases (P = 0·0237). Higher aggregate HAI titer responses were associated with a higher baseline B‐cell count (P = 0·0240), and higher CD4 and CD8 influenza‐specific T‐cell responses, suggesting prior antigen exposure is a significant contributor. The solid tumor cohort had equivalent responses during all time frames of chemotherapy. Discussion: The optimal protection from influenza of pediatric patients on chemotherapy should include vaccination, but it is clear that not all patients produce high titers of antibodies after vaccination. This study identified biomarkers that could be used to individualize vaccine approaches. Immunologic predictors might have a role in targeting resources, as B‐cell counts predicted of vaccine responses among the patients with ALL.